Evaluation of Program for Overcoming Intestinal Worm Infections among Children - Febriyanti, Henny; Idris, Haerawati (UI Scholars Hub, 2020)
Prevalence of intestinal worm infection in generall is extremely high in Indonesia among the poor population with poor sanitation. One of the government programs to address this problem is the distribution of medicines to prevent intestinal worm infections. However, the coverage of the achievement for this program is still low in several areas of public health centers in Palembang. Therefore, this study was conducted to evaluate the efficacy of the national program for preventing intestinal worm infections. The qualitative research design used evaluation model approach Context, Input, Process, and Product (CIPP) model. This study was conducted in one of health centers in Palembang City. The informants were selected using purposive sampling method. Data collection was done via in-depth interviews, document reviews, and observations. Descriptive content analysis was used to examine and process the collected data. Results showed that, from situational factor, the program is held by the government because of the high prevalence of intestinal worm infection. The study found the input component, limited staff that handles this program. There were limited facilities for the extension of the infrastructure. In the process component, the distribution of the drug albendazole was not optimal in all elementary schools. Four elementary schools did not receive albendazole. This study demonstrated that the implementation of the program was not optimal